Development of Interactive Multimedia Modules to Support Inclusive Education in the Learning Planning for Children with Special Needs Course - Badiah, Lutfi Isni; Kurniawan, Andri (JURNAL DIMENSI PENDIDIKAN DAN PEMBELAJARAN, 2025)
Inclusive education necessitates the availability of learning media accessible to all students, including those with visual impairments. This study focused on developing an interactive multimedia module using Articulate Storyline, designed to cater to the needs of visually impaired students and their peers in the Special Education Needs Planning course. The research employed the Research and Development (RD) approach, utilizing the DDD-E model (Decide, Design, Develop, Evaluate). The process encompassed a needs analysis, the design of a module based on the principles of Universal Design for Learning (UDL), module development, and an evaluation of its feasibility and effectiveness. Validation by experts in learning planning, inclusive education, and multimedia design deemed the module highly effective and suitable for use without requiring revisions. Trials involving visually impaired and regular students demonstrated that the module enhanced both understanding and engagement in learning. This interactive multimedia module plays a pivotal role in advancing the implementation of inclusive education within higher education institutions. Further research can explore the application of the developed interactive multimedia module in different courses and broader educational settings to validate its adaptability and effectiveness. Comparative studies between traditional teaching methods and the integration of such modules could provide insights into their impact on learning outcomes, particularly for students with diverse needs.